(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
The present objective for the study was to prepare proliposomal gel bearing a steroidal anti-inflammatory agent, prednisolone intended for topical application. Various proliposome formulations were prepared using thin film hydration technique by varying the lipid phase composition (lecithin/cholesterol). Proliposome formulations were characterized for drug content, entrapment efficiency, surface morphology, surface charge, FTIR and stability studies. Topical proliposomal gels were prepared by incorporation of proliposome into strusctured vehicle carbopol (2%). Alternatively, hydrogels containing prednisolone were prepared and their drug release properties were investigated. Pharmacodynamic activity was also determined for optimized proliposomal gel and was compared with commercial marketed gel. A spherical shape of reconstituted prednisolone liposome with an average vesicle about 2 6μm was observed in photomicrographs. The percentage entrapment of drug was increased with increase in phospholipid composition in the range of 85-98%. FTIR studies showed no possible drug-excipient interaction. Proliposomal gel showed prolonged release of prednisolone than the hydrogels. Anti-inflammatory activity proliposomal gel showed maximum percentage of inhibition of edema 60% when compared to commercial marketed gel 55%. Stability studies indicated that product is stable and should be stored at low temperatures. Proposed prednisolone proliposomal gel showed sustains release with enhanced anti inflammatory activity implicating its potential in effective topical pharmacotherapy for the treatment of rheumatoid arthritis.